JUMPA Vol.2 No.3 Okt 2015 ANALISIS DENGAN MENGGUNAKAN METODE CAMEL TERHADAP KINERJA KEUANGAN BANK BUMN SEBAGAI PENILAIAN TINGKAT KESEHATAN BANK: ANALISIS DENGAN MENGGUNAKAN METODE CAMEL TERHADAP KINERJA KEUANGAN BANK BUMN SEBAGAI PENILAIAN TINGKAT KESEHATAN BANK - Hisvi Dwi Fitrianti Sekolah Tinggi Ilmu Ekonomi YAI jakarta; Abdul Djawad Sekolah Tinggi Ilmu Ekonomi YAI jakarta (Jurnal Manajemen dan Perbankan (JUMPA), 2015)
This study analyzes the financial performance of state-owned banks consisting of Bank Mandiri, BRI, BNI and BTN. in the period 2010-2014 by using CAMEL. Data to be used in this research is the quantitative form of financial statements of Bank Mandiri, BRI, BNI and BTN. 2010-2014. The aim of research to find out and analyze whether there is any difference in the financial performance of the Bank based on data of financial ratios. This research was taking samples or small sample size (n less than 30). Parametric statistical methods used are: Kolmogorof Smirnov Test Variety One Direction (One Way ANOVA). The data was processed with SPSS version 21.0. The results showed that there are significant differences in the banks financial performance government period 2010-2014 in asset quality, management, earnings and liquidity, but there are no significant differences in the banks financial performance government period 2010-2014 in capital. Overall Bank Mandiri, BRI, BNI and BTN has financial financial performance relatively well, and in good health. Although the ratio of KAP and LDR BTN in possisi less good and necessary corrective actions to improve these ratios